Peranan Amelioran Pupuk Organik terhadap Hasil Padi pada Musim Tanam Kedua di Lahan Kering Ngawen Gunungkidul Daerah Istimewa Yogyakarta - Arif Anshori; Agung Iswadi; Sunarya Sunarya; Damasus Riyanto (Research and Development Center for Food, Nutrition and Public Health (P4GKM) LPPM UNS, 2021)
Rice cultivation in the second growing season in dry land at Gunungkidul Special Region of Yogyakarta requires additional irrigation and improvement of physical, chemical and biological soil properties. This study aimed to determine the role of organic fertilizer ameliorant on rice yields during second growing season in dry land. The research was conducted in Sambirejo Watusigar Ngawen Gunungkidul Special Region of Yogyakarta during second growing season from March to July 2019. The study used a Randomized Completely Block Design (RCBD) with 3 treatments in the form of no ameliorant, ameliorant of 2 tons ha-1 and ameliorant 4 tons ha-1, with 5 replications. The results showed that the use of ameliorant 2 tons ha-1 produced rice 5.64 ton ha-1 and ameliorant 4 tons ha-1 produced rice 6.04 ton ha-1, which was significantly higher than without ameliorant which only produced 5.29 ton ha-1 of rice.